Task Value Aware Optimization of Routing for Computing Power Network - Huang, Xiaoyao; Lei, Bo; Wei, Min; Ji, Guoliang; Lv, Hang (IEEE International Symposium on Broadband Multimedia Systems and Broadcasting, 2023)
An appealing technology that merges computing and network resources to offer convergent services is the computing power network, which has attracted a lot of interest. In this paper, we study the task routing problem in the heterogeneous computing power network to minimize the loss of task value of the system. We first formulate the problem as a mixed integer nonlinear programming problem (MINP). To solve the problem, we propose a task Value aware Ant Colony algorithm(VACO) and deduced the complexity of the algorithm. The proposed algorithm VACO searches for optimal traversal in the directed graph by multiple ants for multiple rounds based on the designed task value aware pheromone concentration and transition probability function to achieve the minimum value loss routing scheme. Finally, the proposed algorithm's excellent performance was demonstrated through comprehensive simulations conducted in the end.